Linguistik Forensik Ujaran Kebencian Terhadap Ameena Hanna Nur Atta Di Media Sosial - Duta Ananda Putri; Imtisalun Auliyah; Adi Natal Gabriel Siringo ringo (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
Technological advances that are vulnerable to misuse are the use of social media. Everyone has the freedom to express opinions through various contexts, both physical, psychological, and social. Social media also has a negative impact in the form of hate speech. This research aims to describe the hate speech of a netizen who blasphemed Amina Hanna Nur Atta, daughter of Atta Halilintar and Aurel Hermansyah. This research uses a descriptive qualitative approach. The Data was collected from screenshots taken by the owner of the Instagram account @attahalilintar, which were uploaded and distributed to various social media pages.. The first data obtained was in the form of comments which were categorized as self-deprecating speech for someone with special needs for Down syndrome. The second data is in the form of comments that can give rise to the assumption that children's social abilities are low due to Down syndrome. The third data is included in the category of hate speech and discrimination against individuals with Down syndrome as special needs. Perpetrators of hate speech via social media can be subject to legal sanctions for violating the ITE Law. Hate speech via social media accounts can take the form of taboo words or actions. Taboo words or actions in this study were analyzed using speech acts.